Community occupational therapy for people with dementia and family carers (COTiD-UK) versus treatment as usual (Valuing Active Life in Dementia [VALID] programme): study protocol for a randomised controlled trial. Issue 1 (December 2016) - Wenborn, Jennifer; Hynes, Sinéad; Moniz-Cook, Esme; Mountain, Gail; Poland, Fiona; King, Michael; Omar, Rumana; Morris, Steven; Vernooij-Dassen, Myrra; Challis, David; Michie, Susan; Russell, Ian; et al.
Abstract Background A community-based occupational therapy intervention for people with mild to moderate dementia and their family carers (Community Occupational Therapy in Dementia (COTiD)) was found clinically and cost effective in the Netherlands but not in Germany. This highlights the need to adapt and implement complex interventions to specific national contexts. The current trial aims to evaluate the United Kingdom-adapted occupational therapy intervention for people with mild to moderate dementia and their family carers living in the community (COTiD-UK) compared with treatment as usual. Methods/Design This study is a multi-centre, parallel-group, pragmatic randomised trial with internal pilot. We aim to allocate 480 pairs, with each pair comprising a person with mild to moderate dementia and a family carer, who provides at least 4 hours of practical support per week, at random between COTiD-UK and treatment as usual. We shall assess participants at baseline, 12 and 26 weeks, and by telephone at 52 and 78 weeks (first 40 % of recruits only) after randomisation. The primary outcome measure is the Bristol Activities of Daily Living Scale (BADLS) at 26 weeks. Secondary outcome measures will include quality of life, mood, and resource use. To assess intervention delivery, and client experience, we shall collect qualitative data via audio recordings of COTiD-UK sessions and conduct semi-structured interviews with pairs and occupational therapists. Discussion COTiD-UK is an evidence-based person-centred intervention that reflects the current priority to enable people with dementia to remain in their own homes by improving their capabilities whilst reducing carer burden. If COTiD-UK is clinically and cost effective, this has major implications for the future delivery of dementia services across the UK. Trial registration Current Controlled TrialsISRCTN10748953 Date of registration: 18 September 2014.